Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.2459/jcm.0000000000000500
|View full text |Cite
|
Sign up to set email alerts
|

Takotsubo syndrome and estrogen receptor genes

Abstract: The study reports preliminary findings suggesting a possible link between ESR polymorphisms and the occurrence of TS. Larger studies are needed to confirm our results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 34 publications
0
25
0
Order By: Relevance
“…The highest risk is noted in women carrying a T allele at the rs1271572 locus of the oestrogen receptor 2 gene. 10 A study conducted in ovariectomised female rats has shown that 2 weeks of oestradiol supplementation reduced mortality in rats with TCMP-like cardiac dysfunction. 11 Another study has shown that oestradiol helps protect against the toxic effects of catecholamines on cardiac myocytes.…”
Section: The Role Of Oestrogen Deficiency In the Pathophysiology Of Tmentioning
confidence: 99%
“…The highest risk is noted in women carrying a T allele at the rs1271572 locus of the oestrogen receptor 2 gene. 10 A study conducted in ovariectomised female rats has shown that 2 weeks of oestradiol supplementation reduced mortality in rats with TCMP-like cardiac dysfunction. 11 Another study has shown that oestradiol helps protect against the toxic effects of catecholamines on cardiac myocytes.…”
Section: The Role Of Oestrogen Deficiency In the Pathophysiology Of Tmentioning
confidence: 99%
“…[585960] Eitel et al recently conducted the first genome-wide association study for TCM locating 68 candidate loci,[61] and some preliminary studies have also reported an association with estrogen receptor polymorphisms in both the ESR1 and ESR2 genes. [62] However, it is important to note that larger population studies are necessary to provide statistically significant genetic links for TCM.…”
Section: Etiopathogenesismentioning
confidence: 99%
“…42 In addition, a possible pathophysiological role of some polymorphisms of estrogen receptors a and b genes (Cys397Thr and Gly1839Thr, respectively) that reduce estrogen effects has been postulated. 43 However, recent data showed that TS occurred in postmenopausal women despite hormone replacement therapy 37 and that oophorectomized women did not evidence a worse clinical course, 44 suggesting that hypoestrogenemia itself cannot be the primary cause of TS development, even if it probably plays a protective role. Moreover, men show low estrogen levels throughout their life, so the sudden decrease of estrogen could be an explanation for the postmenopausal development of TS in women, but cannot explain why females are significantly more prone to TS than males.…”
Section: Ts and Gender: Does It Really Matter?mentioning
confidence: 99%